A penetração capitalista no Acre e no emprego industrial urbano em Rio Branco - Oliveira, Marilda Maia (1983)
The territorial annexation of the State of Acre to Brazil and its human occupation in the late eighteenth century were the results of an economic activity - vegetal rubber extraction -- at that moment led by the mercantile capital. The migration process throughout the years has been a consequence of the vegetal rubber economy which, up to the ad of the 30's, was altogether linked to the external markets. Only in the 40's the Brazilian Government turned its a tention to the vegetal rubber activity determining a new flow of labor force to the "seringais" (large land proporties containing the rubber trees) of Acre. This was a result of new forms of recruting labor mainly from the Northeastern region such as as the "rubber soldier"system through_ which individuals could avoid the mili tary draft by migrating to the Northern region in order to work on rubber latex extraction. In the 70's the capitalistic interests of the enter-South region determined some drastic transformations in the existing forms af social, economic. and cultural organization. The core of this study consists in the historical reconstituion of the social and economic trajectory of the labor force as a basis to verify the actual level of the urban labor force absorption by the industrial sector, specially through the Industrial District of Rio Branco (state of Acre's capital), as well the participation of the migrant labor force in that sector. This urban labor is composed mainly of fome agricultural workers, rubber latex extractors ("seringueiros") and land tenants now crowded in the poor slums of the city. We,also try to analyze, in a general way, the performance of urban exployment in Rio Branco from the beginning of the 70's. These problems have attained a great importance to that city, since its development patterns are reflecting an accelerated urbanization process which has led to a universalization of wage earning labor as well as a greater labor force absorption. The main subject is analyzed in various chapters which, basically, discuss the theoretical aspects concerning the determination'of the employment leveI in backward economies the general characteristics of the development process of the economy of the State of Acre, since its formation; analysis of some relationships between the economy of Acre and the Brazilian economy the analysis of most recent economic transformations in the city of Rio Branco the composition of the urban employment in Rio Branco and, finally, the performance of the Industrial District of Rio Branco concerning its role in solving the socio-economic problems of the area using the results of a sur vey of Rio Branco's industrial sector. ~